Problems Of Islamic Religious Education Learning During The Covid-19 Pandemic At SMA Muhammadiyah 1 Muntilan - Wahyu Ari Wibowo; Achmad Anugrah Faisal; Imron Imron (Jurnal Mantik, 2022)
At this time all countries in all corners of the world are being hit by a major disaster caused by the Covid-19 virus. The Covid-19 virus has had an impact on the world of education, including Islamic religious education. In an emergency situation like this, Islamic religious education learning still has a very important role for students when facing the Covid-19 pandemic. Because in essence the purpose of learning Islamic religious education is to increase the faith, understanding, appreciation and practice of students about the religion of Islam so that they become Muslim human beings who believe and fear Allah SWT and have noble character in personal, social, national and state life. The purpose of this study was to identify the problems of learning Islamic religious education in online teaching and learning activities during the Covid-19 pandemic. This study uses a field research method (Field Research) and uses a descriptive qualitative approach. The data collection techniques used in this study were interviews and observations. While the data analysis in this study used qualitative data presented without calculating numbers. The respondent of this research is one of the homeroom teachers and students of class X at SMA Muhammadiyah 1 Muntilan.